Refractory constrictive pericarditis caused by an immune checkpoint inhibitor properly managed with infliximab: a case report. Issue 1 (1st February 2021) - Moriyama, Shohei; Fukata, Mitsuhiro; Tatsumoto, Ryoma; Kono, Mihoko
Abstract: Background: Immune checkpoint inhibitors (ICIs) can cause cardiac immune-related adverse events (irAEs), including pericarditis. Cardiovascular events related to pericardial irAE are less frequent, but fulminant forms can be fatal. However, the diagnosis and treatment strategies for pericardial irAE have not established. Case summary: A 58-year-old man was diagnosed with advanced non-small-cell lung cancer and nivolumab was administered as 5th-line therapy. Eighteen months after the initiation of nivolumab, the patient developed limb oedema and increased body weight. Although a favourable response of the cancer was observed, pericardial thickening and effusion were newly detected. He was diagnosed with irAE pericarditis after excluding other causes of pericarditis. Nivolumab was suspended and a high-dose corticosteroid was initiated. However, right heart failure (RHF) symptoms were exacerbated during the tapering of corticosteroid because acute pericarditis developed to steroid-refractory constrictive pericarditis. To suppress sustained inflammation of the pericardium, infliximab, a tumour necrosis factor-alfa inhibitor, was initiated. After the initiation of infliximab, the corticosteroid dose was tapered without deterioration of RHF. Exacerbation of lung cancer by irAE treatment including infliximab was not observed. Discussion: IrAE should be considered when pericarditis develops after the administration of ICI even after a long period from its initiation. Infliximab rescue therapy may be considered as a 2nd-line therapy for steroid-refractory irAE pericarditis even with constrictive physiology.